REGULARITIES OF THE FLOW OF SINGLE FREIGHTAGES FOR THE INTERCITY FREIGHT TRANSPORTATION - Mospan, N.; Мосьпан, Н. В. (Харьковский национальный автомобильно-дорожный университет, 2016)
It was experimentally proved that a number of single intercity freightages in Ukraine is dis-tributed by the Poisson law. And a single freightage flow in conditions of its occurrence corre-sponds to the simplest flow and is actually the simplest one. Due to the fact this flow is the result of a big number of different shippers’ activityies, formation of an single intercity freightage is a rare event for each of them.
ЗАКОНОМЕРНОСТИ ПОТОКА РАЗОВЫХ ЗАЯВОК НА МЕЖДУГОРОДНЫЕ ГРУЗОПЕРЕВОЗКИ
ЗАКОНОМІРНОСТІ ПОТОКУ РАЗОВИХ ЗАМОВЛЕНЬ НА МІЖМІСЬКІ ВАНТАЖОПЕРЕВЕЗЕННЯ
Keywords: flow; single freightage; intercity freight transportation; Kolmogorov-Smirnov test; поток; разовая заявка; междугородная грузоперевозка; критерий Колмогорова-Смирнова; потік; разове замовлення; міжміське вантажоперевезення; критерій Колмогорова-Смирнова; 656.[95+136]